Financial Management Behaviour of MSMEs in Buleleng Regency - The Mediating Role of Financial Self Efficacy - Ni Made Sri Ayuni; Ni Nyoman Juli Nuryani; Made Dwi Ferayani; Ni Wayan Novi Budiasni; Sebastian Herman; Alexandra Maria Pires (Universitas Pendidikan Nasional, 2026)
This study examines the influence of financial literacy, financial inclusion, and financial attitude on the financial management behavior of MSMEs in Buleleng Regency, with financial self-efficacy serving as a mediating variable. A quantitative research design was applied using survey data collected from 100 MSME owners through structured questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Despite the relatively limited sample size for a model involving multiple latent constructs and hypotheses, the application of bootstrapping in SEM-PLS provided stable and reliable parameter estimates. The findings reveal that financial literacy and financial attitude significantly improve financial management behavior. Financial inclusion was not found to have a direct influence on financial management behavior; however, it significantly enhances financial self-efficacy. In addition, financial self-efficacy has a positive and significant effect on financial management behavior and mediates the relationships between financial literacy, financial inclusion, financial attitude, and financial management behavior. These results indicate that psychological confidence plays a crucial role in translating financial knowledge, financial access, and financial attitudes into effective financial practices among MSME actors. The study implies that MSME empowerment programs should integrate financial education, inclusion initiatives, and confidence-building strategies such as mentoring and practical financial training. However, this study is limited by the relatively small sample size and its focus on MSMEs within a single regional context, which may restrict the broader generalizability of the findings.